BODY MASS INDEX AS A PREDICTOR OF EXERCISE CAPACITY AMONG POSTPARTUM WOMEN: A CROSS-SECTIONAL STUDY - Rabiatul Adawiah Abdul Rahman; Nurul Husna Mohd Nasir (The Indonesian Journal of Public Health, 2025)
Introduction: Maternal obesity is a major global health issue, affecting 14.6% of women in Malaysia. An abnormally higher body mass index (BMI) is associated with various health problems, including reduced exercise capacity, affecting daily activities. During the postpartum period, BMI and exercise capacity significantly impact women's fitness and risk of other health problems. Yet, the predictor of exercise capacity related to BMI is not well defined and understood. The study aims to determine the level of exercise capacity and its predictor among postpartum women. Methods: A cross-sectional study was conducted at Kepala Batas Health Clinic, Pulau Pinang. A total of 134 postpartum women were recruited using a purposive sampling method. Descriptive analysis was performed on data pertaining to sociodemographic characteristics, anthropometric characteristics, and exercise capacity level as measured by the 2-Minute Step Test (2MST). Predictors of exercise capacity were analyzed using a stepwise linear regression test. Results: Overall, the mean BMI was 24.7 ± 4.9 kg/m² and the mean score of exercise capacity based on 2MST was 87.93 ± 9.89 heart beats per minute, which was good. The strongest significant predictor of exercise capacity among postpartum women is being overweight (R² = 80.1%). Higher BMI leads to more musculoskeletal pain, inflammation, and fatigue, hindering exercise and physical activity. Conclusions: Postpartum women with an abnormal BMI should be provided with comprehensive intervention by a multidisciplinary team, particularly physiotherapy and dietitian. This intervention is crucial for preserving exercise capacity, which serves as a fundamental indicator of a woman's overall physical fitness.